Granice kontroli sądowej odwołania uczestnika postępowania nominacyjnego przed Krajową Radą Sądownictwa przez Sąd Najwyższy, w świetle jego orzecznictwa - Demendecki, Tomasz (PRAWO i WIĘŹ, 2024)
Adoption in Art. 44 section 3 of the Act of 2011 on the National Council of the Judiciary that the provisions of the Code of Civil Procedure on cassation appeals shall apply to proceedings before the Supreme Court in cases involving appeals against decisions of the Council implies the method of determining the limits of the Supreme Court’s examination of a case initiated by an appeal of a party to the proceedings. The jurisdiction of the Supreme Court in cases involving appeals against the decisions of the National Council of the Judiciary on the appointment of judges includes, first of all, the examination of the inconsistency of the decision with the law. Although the Supreme Court does not have the authority to examine the merits of candidates for judicial office, nor to decide which of them should be submitted to the President of the Republic of Poland with an application for appointment as a judge, the subject of the procedure for evaluating a candidate and submitting an application for his appointment as a judge is a matter within the meaning of Article 45(1) of the Constitution and is therefore subject to judicial review to the extent appropriate to this type of case, i.e. in terms of legality and compliance with the applicable legal procedures.